2020
DOI: 10.2147/ijgm.s244472
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of Serum Levels of Vitamin D with Blood Pressure Status in Northern Iranian Population: The PERSIAN Guilan Cohort Study (PGCS)</p>

Abstract: Background: Evidence in the last decades has indicated an association between vitamin D and cardiovascular risk factors including blood pressure. The present study aimed to determine whether serum 25-hydroxyvitamin D is independently associated with blood pressure in a large population-based study. Methods: The study was based on subjects from PERSIAN Guilan Cohort Study (PGCS), a prospective, population-based cohort study in Guilan, Iran. In 9520 men and women, aged 35-70 years, serum 25-hydroxyvitamin D, sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
2
16
1
Order By: Relevance
“…Validation of other measurements such as blood pressure instruments has been performed in previous studies [ 25 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Validation of other measurements such as blood pressure instruments has been performed in previous studies [ 25 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Validation of other measurements such as blood pressure instruments has been performed in previous studies [ 33 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…[17]. Joukar F conducted a prospective cohort study that found the relationship between vitamin D levels and SBP was weak but statistically negative, and there was no signi cant relationship between vitamin D levels and DBP [18].…”
Section: Discussionmentioning
confidence: 99%